Model Prediksi Financial Distress Perusahaan Go Public di Indonesia (Studi pada Sektor Manufaktur) - Iramani, Rr. (Universitas Brawijaya, Indonesia, 2008)
The objective of this research is to examine financial ratios of accrual basis, financial ratios of cash basis, industry relative ratios of accrual basis, industry relative ratios of cash basis and sensitivity toward macro economic indicators as financial distress predictors and to develop a financial distress prediction model as early warning system for go-public enterprises in Indonesia. From the analysis, it was found out that the significant variables in terms of forming prediction model to be successful is interpreted, consisting of four financial ratios of accrual basis variables, two industry relative ratios of accrual basis variables and one industry relative ratios of cash basis variable. This financial distress prediction model is as the following: Py1 = 1/1+e-(-0.5-0.6RETA+1.27TDTA-1.OSEATS+2.18INVNS-0.35RSEBITTA-0.42RSSTA 0.44RSCFTL)